Pengaruh Efikasi Diri Dan Beban Kerja Terhadap Kinerja Melalui Kepuasan Kerja Pergawai Pada Kantor Dinas Ketahana Pangan Dan Peternakan Provinsi Sumatera Utara - Jane Margarentha Sembiring (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The purpose of this study was to examine and analyze the effect of self-efficacy and workload on employee performance through job satisfaction at the Office of Food Security and Animal Husbandry of North Sumatra Province directly or indirectly. The approach used in this study is a causal approach. The population in this study were all state civil servants at the Office of Food Security and Animal Husbandry of North Sumatra Province. The sample in this study used a sample of the Slovin formula totalling 69 state civil servants at the Office of Food Security and Animal Husbandry of North Sumatra Province. Data collection techniques in this study used documentation, observation, and questionnaire techniques. The data analysis technique in this study uses a quantitative approach using statistical analysis by using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results of this study prove that directly self-efficacy, workload and job satisfaction have a significant effect on employee performance and indirectly self-efficacy and workload have a significant effect on employee performance through job satisfaction at the Office of Food Security and Animal Husbandry of North Sumatra Province.